Waste Workers and Pickers: Neglected Highrisk Groups in Developing Countries During the COVID-19 Pandemic - Vahid Kazemi Moghaddam; Tony R. Walker; Manizhe Pakdel; Parvin Ahmadinejad; Ali Akbar Mohammadi (Journal of Health Sciences and Surveillance System, 2023)
The COVID-19 pandemic has induced some negative environmental issues, especially in the waste management sector. In developing countries, handling waste is carried out by two groups: waste workers and waste pickers who are exposed to possible hazards of infected waste. In the present narrative review, we searched for high-quality English publications in PubMed, Scopus, and Embase databases. The COVID-19 pandemic led to several problems in waste management systems, especially in developing countries. Due to poor management systems, waste workers and pickers are likely exposed to health risks related to unhealthy waste handling. The support of governments is urgently required to properly inform ordinary people about the correct ways of disposing of PPE and also train sanitation workers and waste pickers to reduce the hazardous possibilities. Additionally, financial support can also act as a suppressive agent to reduce the number of waste pickers.